2020
DOI: 10.1038/s41598-020-73311-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of Ca12Ga14O33

Abstract: Ca12Ga14O33 was successfully synthesized using a wet chemistry technique to promote the homogenous mixing of the Ca and Ga cations. Rietveld refinements on X-ray and neutron powder diffraction data confirm that the compound is isostructural to Ca12Al14O33, however, with a significantly larger lattice parameter allowing for the cages that result from the framework arrangement to expand. In naturally occurring Ca12Al14O33, the mineral mayenite, these cages are occupied by O2− anions, however, experimental studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Therefore, replacing Al atoms with Ga ions with less rigidity and meanwhile with a larger ionic radius, which would expand the width of the windows, is expected to result in higher conductivity. Unfortunately, as observed in our experiments, the conductivities of these high-level Ga-doped samples did not show apparent enhancement, although the width of the windows between cages increased with the gallium content, as displayed in Figure S14, and similar expansion was also observed for the cages in Ca 12 Ga 14 O 33 with the mayenite structure when compared to that of the Ca 12 Al 14 O 33 material . It may indicate that the rigidity of the framework cations and the width of the windows between cages are not key factors for improving oxide-ion conductivity in the mayenite Ca 12 Al 14 O 33 -based materials.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Therefore, replacing Al atoms with Ga ions with less rigidity and meanwhile with a larger ionic radius, which would expand the width of the windows, is expected to result in higher conductivity. Unfortunately, as observed in our experiments, the conductivities of these high-level Ga-doped samples did not show apparent enhancement, although the width of the windows between cages increased with the gallium content, as displayed in Figure S14, and similar expansion was also observed for the cages in Ca 12 Ga 14 O 33 with the mayenite structure when compared to that of the Ca 12 Al 14 O 33 material . It may indicate that the rigidity of the framework cations and the width of the windows between cages are not key factors for improving oxide-ion conductivity in the mayenite Ca 12 Al 14 O 33 -based materials.…”
Section: Resultssupporting
confidence: 51%
“…McCoy et al recently reported that the composition of Ca 12 Ga 14 O 33 with the mayenite-type structure can be obtained through a polymer assisted sol–gel synthesis method . The amorphous precursor would crystallize into the pure mayenite phase only within a narrow temperature range of 750–975 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations